Online multidisciplinary discussion on interstitial lung disease: Using new technologies to connect general hospitals to expert units - Francesqui, Joel; Benegas, Mariana; Laserna, Elena; Valera, Leticia; Cuerpo, Sandra; Hernández-González, Fernanda; Serrano, Mario; Sánchez, Marcelo; Sellares, Jacobo (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
.